Penyaluran Dana Bank Syariah Melalui Pembiayaan Murabahah, Istishna, dan Ijarah Sebelum dan Selama Pandemi Covid 19 - Taudlikhul Afkar; Teguh Purwanto (Jurnal Ilmiah Ekonomi Islam, 2021)
Impact of the Covid-19 pandemic in Indonesia is not only in the productive sector but has an impact on the financial sector such as conventional and Islamic financial institutions including banking. Islamic banks have business activities through murabaha, istishna', and ijara financing for sale and purchase and lease types. The impact felt by the banking sector can be seen from the existence of financing problems. The purpose of this research is to compare the conditions of sharia financing before and during the Covid-19 pandemic. The method used is the paired sample t-test with a sample of Islamic banks in Indonesia. The results show murabaha and istisna' financing has increased, while ijara financing has decreased during the Covid-19 pandemic.